2019
DOI: 10.3389/fpsyg.2019.01052
|View full text |Cite
|
Sign up to set email alerts
|

Lived Experience in New Models of Care for Substance Use Disorder: A Systematic Review of Peer Recovery Support Services and Recovery Coaching

Abstract: Peer recovery support services (PRSS) are increasingly being employed in a range of clinical settings to assist individuals with substance use disorder (SUD) and co-occurring psychological disorders. PRSS are peer-driven mentoring, education, and support ministrations delivered by individuals who, because of their own experience with SUD and SUD recovery, are experientially qualified to support peers currently experiencing SUD and associated problems. This systematic review characterizes the existing experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
202
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(205 citation statements)
references
References 51 publications
2
202
0
1
Order By: Relevance
“…Peers were able to build rapport based on commonalities and promote harm reduction efforts in the community. Studies conducted in emergency departments and clinical settings in the US and in other contexts globally have similarly reflected the acceptability and potential for peers in harm reduction and recovery support services, including for reduction of use, decreased risk behaviors, and improved quality of life [26,[60][61][62][63][64][65][66][67]. Particularly considering some stigmatizing interactions with health care workers, as one client noted above, individuals may be better able to share experiences and address underlying factors contributing to problematic substance use when working with a PRC.…”
Section: Discussionmentioning
confidence: 99%
“…Peers were able to build rapport based on commonalities and promote harm reduction efforts in the community. Studies conducted in emergency departments and clinical settings in the US and in other contexts globally have similarly reflected the acceptability and potential for peers in harm reduction and recovery support services, including for reduction of use, decreased risk behaviors, and improved quality of life [26,[60][61][62][63][64][65][66][67]. Particularly considering some stigmatizing interactions with health care workers, as one client noted above, individuals may be better able to share experiences and address underlying factors contributing to problematic substance use when working with a PRC.…”
Section: Discussionmentioning
confidence: 99%
“…We have thus assessed sample sizes, data collection methods, and perceived limitations of each included paper, although we did not use a formal quality assessment tool. The 62 included studies consisted of one grey literature report [27], 49 primary studies ( ), including quantitative, qualitative, mixed methods and feasibility studies, three study protocols ( [80][81][82]), four reviews ( [26,[83][84][85]), three commentaries ( [86][87][88]), and two case studies ( [89,90]). Sample sizes in the 52 primary studies ranged from n = 4 to n = 948.…”
Section: Quality Appraisal and Study Detailsmentioning
confidence: 99%
“…Outcomes of peer-delivered interventions in HICs are generally positive: for instance, a recent study on "recovery coaches" for patients with SUD showed a decrease in acute care visits and an increase in engagement in buprenorphine treatment (Magidson et al 2019b). There is, however, an overall lack of rigorous studies, and results are difficult to generalize or replicate due to variability in peer role and training (Davidson et al 1999;Eddie et al 2019). Although peers are not uncommon in HICs, there is still considerable work needed to develop, test, and scale the role.…”
Section: Closing the Behavioral Health Treatment Gap: Task Sharing Wimentioning
confidence: 99%
“…Many questions remain about how to best integrate peers into the broader healthcare workforce and system for SUD and other mental health care (Kent 2019). While peers have long been part of behavioral health care in HICs (Davidson et al 1999;Eddie et al 2019;Kent 2019;Myrick and Del Vecchio 2016;Salzer et al 2010), they are rarely employed in LMICs (Magidson et al in press). As HICs continue to develop and standardize peer recovery models, LMICs could learn from and adapt models of task sharing that emphasize support from people who share a diagnosis, while HICs borrow and adapt strategies that LMICs have used to develop and scale-up CHW programs.…”
Section: Closing the Behavioral Health Treatment Gap: Task Sharing Wimentioning
confidence: 99%